Aluminum alloy and preparation method and application thereof

By adjusting the composition and preparation process of aluminum alloy, the performance reduction problems caused by high Fe, Mn and Si elements are solved, and a medium-strength and excellent formability aluminum alloy is achieved, reducing production costs and energy consumption, and is suitable for automotive bodywork Inner plates, rail transit tools and other fields.

CN118703846BActive Publication Date: 2025-01-07WEIQIAO LIGHTWEIGHT RESEARCH CENTER AT SOOCHOW
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411194594.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-29
Publication Date
2025-01-07
Estimated Expiration
2044-08-29

AI Technical Summary

Technical Problem

The existing 5754 aluminum alloy has a reduced performance under high Fe, Mn and Si element content, which limits its application in automotive body inner panels, rail transit tools and other fields. The energy consumption of recycling recycled aluminum alloy is high and the production cost is high. Larger.

Method used

By adjusting the composition of the aluminum alloy, increasing the content of elements such as Mg, Cu, Cr, Zn, etc., and homogenizing, hot rolling and cold rolling deformation during the preparation process, controlling the size and distribution of the iron-rich phase and Mg2Si phase to form Refined diffused phase particles improve the strength and shaping properties of the alloy.

Benefits of technology

With high Fe, Mn and Si element content, the medium strength and excellent formability of aluminum alloys are achieved, which reduces production costs and improves the efficiency of recycling and reuse, and meets the performance requirements of 5754 aluminum alloy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118703846B_ABST
    Figure CN118703846B_ABST
Patent Text Reader

Abstract

The invention discloses an aluminum alloy and a preparation method and application thereof. The aluminum alloy, in an Al-Mg alloy system, simultaneously contains Mn, Cr, Cu, Zn and X element (at least two of Sr, Mo and Zr) by optimizing the alloy formula, and further controls their contents. The combination can weaken the damage of coarse second phase particles to strength and forming performance, and improve the tolerance of the alloy to impurity elements such as Fe and Si and Mn element. Therefore, recycled materials can be used for production, and the proportion of original aluminum used is reduced. The aluminum alloy itself has very good recyclability, is economical, low-carbon and energy-saving. During preparation, the aluminum alloy is first made into an ingot, and then subjected to homogenization treatment, hot rough rolling, hot finish rolling, cold rolling and annealing treatment. Practice shows that the aluminum alloy of the invention at least achieves a balance of alloy properties such as tensile strength, yield strength and elongation after fracture, and can be used in the fields of preparing automobile body parts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of aluminum alloys, and in particular to an aluminum alloy and a preparation method and application thereof. Background Art

[0002] 5754 aluminum alloy is a non-heat-treatable aluminum alloy that is mainly strengthened by solid solution strengthening and work hardening of atoms such as Mg. It is a typical alloy in the Al-Mg series alloys. Due to its medium strength, good formability, corrosion resistance and weldability, it is widely used in the fields of automobiles, rail transportation, ships, etc.

[0003] At present, 5754 aluminum alloy usually strictly limits impurity elements such as Fe and Si, and controls the Mn content at a low level to ensure the strength, formability, surface quality or conductivity of the alloy. For example, patent CN113337760A discloses a method for improving the O-state conductivity of 5754 alloy, in which Si≤0.10wt.%, Fe≤0.10wt.%, Cu≤0.10wt.%, Mn=0.10wt.%~0.12wt.%, Mg=2.6wt.%~2.7wt.%, Cr≤0.001wt.%, Zn≤0.001wt.%, Ti≤0.001wt.%, and the rest are Al and other unavoidable elements, and the single element of the other unavoidable elements is ≤0.05wt.%, and the total is ≤0.15wt.%; for example, CN1170 11913A discloses a 5754-O aluminum alloy sheet for automotive structural parts and a production method. In the alloy, Si≤0.1wt.%, Fe≤0.2wt.%, Cu≤0.08wt.%, Mn=0.25wt.%~0.4wt.%, Mg=2.8wt.%~3.4wt.%, Cr=0.05wt.%~0.2wt.%, Zn≤0.2wt.%, Ti≤0.025wt.%, and the remainder is Al and other impurity elements. The other impurity elements include V, Zr, Be, B, Li, Na, Ca, Pb, Sn, and Bi, with a total content of ≤0.15wt.%.

[0004] The energy consumption of recycled aluminum alloy is only 4% to 6% of that of electrolytic aluminum, which is one of the most efficient ways to achieve energy conservation and emission reduction. However, the reduction in alloy performance caused by the high content of Fe, Mn, Si and other elements in recycled aluminum alloy has long been an important reason for limiting its application in the fields of automotive body inner panels or rail transportation vehicles.

[0005] Specifically, Fe is the main impurity in aluminum alloys. According to the Al-Fe binary phase diagram, the maximum solubility of Fe in the aluminum matrix at room temperature is basically 0.025wt.%. Therefore, during the solidification process, Fe atoms will form needle-shaped iron-rich intermetallic compounds Al3Fe. Due to its brittle characteristics and stress concentration caused by the needle-shaped morphology, this type of intermetallic compound is considered to be the most harmful to the mechanical properties of the alloy. At the same time, Mn is usually added to aluminum alloys to compensate for the negative effects of the iron-rich intermetallic compound Al3Fe. After adding Mn to the low-Fe alloy, the long needle-shaped Al3Fe phase transforms into the Chinese character-shaped Al6(Fe,Mn). It is generally believed that the Chinese character-shaped intermetallic compound has little effect on the mechanical properties of the alloy. In addition, Mn improves the comprehensive properties of the alloy by solid solution strengthening and dispersion strengthening. However, in aluminum alloys with high Fe content, as the Mn content increases, the size and number of the intermetallic compound Al6(Fe,Mn) will also increase, and it will show a complex morphology of fishbone, flower, and coarse blocks, which will significantly reduce the mechanical properties of the alloy. The presence of Si in the recycled aluminum alloy, in addition to forming a coarse Mg2Si phase, will also form long needle-shaped Al5FeSi, Al8Fe2Si and the like with Fe, which seriously reduces the plasticity and strength of the alloy.

[0006] Therefore, when the content of impurity Fe in the alloy system is low, the presence of Mn and Si has little effect on the alloy, and the presence of Mn even improves the performance of the alloy to a certain extent. However, once the content of impurity Fe increases, it is equivalent to amplifying the negative impact of Mn and Si, which will cause a greater deterioration in the performance of the alloy. And because the recycled aluminum alloy usually has high contents of Fe, Si, and Mn at the same time, it brings about a coarse-sized and complex-morphology Fe-rich phase, which significantly reduces the strength and plasticity of the alloy, seriously limiting the recycling and reuse of aluminum alloys. Summary of the invention

[0007] The object of the present invention is to overcome one or more deficiencies in the prior art and to provide an improved aluminum alloy which has a high tolerance to elements such as Fe, Mn, Si, and has good strength and plasticity matching. Based on the aforementioned characteristics, even if recycled aluminum alloys (such as recycled cans, automobile plates, etc.) are used, an aluminum alloy with medium strength and excellent formability can be produced, which can be used to replace 5754 aluminum alloy, which not only saves energy and reduces emissions, but also reduces production costs.

[0008] The present invention also provides a method for preparing the above-mentioned aluminum alloy having high tolerance to elements such as Fe, Mn, Si, and having good strength and plasticity matching, and its application in the fields of automobile body parts (such as automobile body inner panels), rail transportation vehicle structures or ship structures.

[0009] In order to achieve the above object, a technical solution adopted by the present invention is:

[0010] An aluminum alloy, comprising, in weight percentage, 2.0 wt.% to 3.2 wt.% of Mg, 0.05 wt.% to 0.3 wt.% of Cu, 0.4 wt.% to 1.2 wt.% of Mn, 0.05 wt.% to 0.3 wt.% of Cr, 0.01 wt.% to 0.3 wt.% of Zn, less than or equal to 0.15 wt.% of Ti, 0 to 0.14 wt.% of X1, 0 to 0.14 wt.% of X2, 0 to 0.14 wt.% of X3, and impurities;

[0011] The impurities include Fe, Si and other impurities except Fe and Si; in terms of weight percentage, in the aluminum alloy, Fe is 0.35wt.% to 0.7wt.%, Si is 0.1wt.% to 0.4wt.%, and the total content of other impurities is less than or equal to 0.2wt.%;

[0012] The Al content is adjusted so that the total amount of the aluminum alloy is 100wt.%;

[0013] Wherein, the X1, X2, and X3 are independently selected from Sr, Mo, and Zr, the X1, X2, and X3 are different and at least two exist at the same time, and the total amount of the X1, X2, and X3 is less than or equal to 0.15wt.%.

[0014] According to the present invention, in some implementation cases, in the cast structure of the aluminum alloy, the area percentage of the iron-rich phase is less than or equal to 3.5%, and the average equivalent diameter is less than or equal to 3.5 μm.

[0015] The iron-rich phase usually refers to the iron-containing phase, such as Al x (FeMn), α-Al(FeMnCr)Si, β-AlFeSi, etc.

[0016] According to the present invention, in some implementation cases, in the cast structure of the aluminum alloy, the area percentage of the Mg2Si phase is less than or equal to 1.5%, and the average equivalent diameter is less than or equal to 1.2 μm.

[0017] According to the present invention, in some implementation cases, in the microstructure of the aluminum alloy in the O state (the O state is a state of the aluminum alloy, i.e., an aluminum alloy product after complete annealing), the average equivalent diameter of the iron-rich phase is 0.8~1.5μm.

[0018] In some embodiments of the present invention, the alloy structure of the aluminum alloy includes dispersed particles, and the dispersed particles include:

[0019] (1) A combination of one or more selected from Al6Mn dispersed phase particles, Al4Mn dispersed phase particles, Al6(FeMn) dispersed phase particles, Al(FeMnCr)Si dispersed phase particles, and Al7Cr dispersed phase particles;

[0020] (2) Selected from Al 12 Mo dispersed phase particles, Al 38 Mg 58 Two or three of Sr4 dispersed phase particles and Al3Zr dispersed phase particles.

[0021] According to the present invention, the average equivalent diameter of the dispersed particles is less than or equal to 100 nm, and the number density of the dispersed particles is 5-20 / μm 2 , further 8-15 / μm 2 .

[0022] According to some preferred aspects of the present invention, the total amount of Mg, Cu and Mn is greater than or equal to 2.5 wt.%.

[0023] According to some preferred aspects of the present invention, the aluminum alloy contains, in terms of weight percentage: 2.0wt.% to 3.0wt.% Mg, 0.05wt.% to 0.3wt.% Cu, 0.5wt.% to 1.2wt.% Mn, 0.05wt.% to 0.3wt.% Cr, 0.05wt.% to 0.25wt.% Zn, less than or equal to 0.1wt.% Ti, 0 to 0.12wt.% X1, 0 to 0.12wt.% X2, 0 to 0.12wt.% X3, and 0.4wt.% to 0.7wt.% Fe, 0.15wt.% to 0.4wt.% Si, and less than or equal to 0.15wt.% other impurities, and the Al content is adjusted so that the total amount of the aluminum alloy is 100wt.%.

[0024] Furthermore, in terms of weight percentage, the aluminum alloy comprises: 2.0wt.% to 3.0wt.% Mg, 0.05wt.% to 0.3wt.% Cu, 0.6wt.% to 1.0wt.% Mn, 0.05wt.% to 0.3wt.% Cr, 0.15wt.% to 0.25wt.% Zn, 0.02wt.% to 0.06wt.% Ti, 0.01wt.% to 0.12wt.% X1, 0.01wt.% to 0.12wt.% X2, 0.01wt.% to 0.12wt.% X3, and 0.4wt.% to 0.7wt.% Fe, 0.15wt.% to 0.4wt.% Si, and less than or equal to 0.15wt.% of other impurities, and the Al content is adjusted so that the total amount of the aluminum alloy is 100wt.%.

[0025] According to some preferred aspects of the present invention, the ratio of the total amount of Mg and Mn to the content of Cr is 10-70:1.

[0026] According to some preferred aspects of the present invention, the ratio of Mg content to Cu content is 8-55:1.

[0027] In the present invention, the aluminum alloy in the O state has a yield strength greater than or equal to 140 MPa, a tensile strength greater than or equal to 260 MPa, and an elongation after fracture greater than or equal to 20%.

[0028] Furthermore, in the O state, the aluminum alloy has a yield strength greater than or equal to 145 MPa, a tensile strength greater than or equal to 260 MPa, and an elongation after fracture greater than or equal to 21.5%.

[0029] According to a specific aspect of the present invention, the aluminum alloy is a 5 series aluminum alloy.

[0030] Another technical solution provided by the present invention is a method for preparing the aluminum alloy described above, the method comprising:

[0031] Providing an aluminum alloy melt containing at least 50 wt.% of recycled aluminum alloy material, and forming the aluminum alloy melt into an aluminum alloy ingot;

[0032] Performing homogenization treatment on the aluminum alloy ingot to obtain a first intermediate;

[0033] Performing a first hot rolling on the first intermediate, and controlling the deformation amount of a single pass of the first hot rolling to be greater than or equal to 5%, and the total deformation amount to be greater than or equal to 90%, to obtain a second intermediate;

[0034] Performing a second hot rolling on the second intermediate, controlling the total deformation to be greater than or equal to 85%, to obtain a third intermediate;

[0035] The third intermediate is subjected to cold rolling deformation with a deformation amount of 60% to 90%;

[0036] Annealing treatment.

[0037] In some embodiments of the present invention, the content of recycled aluminum alloy material in the aluminum alloy melt is greater than or equal to 70%, for example, it can be greater than or equal to 75%, greater than or equal to 80%, greater than or equal to 85%, greater than or equal to 90%, and so on.

[0038] In some embodiments of the present invention, the content of recycled aluminum alloy material in the aluminum alloy melt is greater than or equal to 95%, for example, it can be greater than or equal to 96%, greater than or equal to 97%, greater than or equal to 98%, and so on.

[0039] According to some preferred aspects of the present invention, the temperature of the homogenization treatment is 480-540° C. and the treatment time is 2-12 h.

[0040] According to some preferred aspects of the present invention, in the first hot rolling, the deformation amount in a single pass is greater than or equal to 6%, and the total deformation amount is greater than or equal to 93%.

[0041] According to some preferred aspects of the present invention, in the second hot rolling, the total deformation is controlled to be greater than or equal to 88%.

[0042] According to some preferred aspects of the present invention, the annealing temperature of the annealing treatment is 320-400°C and the insulation time is 2-6h, or the annealing treatment is carried out on a continuous annealing line, heated to 460-520°C and the insulation time is 0-120s. In the present invention, 0s means that the room temperature sheet is heated to the target annealing temperature (e.g. 460-520°C) in the furnace from entering the furnace to leaving the furnace, without staying at this temperature for insulation. This process can be implemented on a continuous annealing line (e.g. a continuous air cushion annealing furnace).

[0043] In some embodiments of the present invention, in the first hot rolling, the start rolling temperature is 400-500°C; in the second hot rolling, the finish rolling temperature is 320-360°C.

[0044] Another technical solution provided by the present invention is: a 5 series aluminum alloy, which comprises, by weight percentage: 2.0wt.% to 3.2wt.% Mg, 0.05wt.% to 0.3wt.% Cu, 0.6wt.% to 1.2wt.% Mn, 0.05wt.% to 0.3wt.% Cr, 0.01wt.% to 0.3wt.% Zn, less than or equal to 0.15wt.% Ti, 0.02wt.% to 0.14wt.% Sr, 0.02wt.% to 0.14wt.% Zr, and impurities;

[0045] The impurities include Fe, Si and other impurities except Fe and Si; in terms of weight percentage, in the 5 series aluminum alloy, Fe is 0.4wt.% to 0.7wt.%, Si is 0.1wt.% to 0.4wt.%, and the total content of other impurities is less than or equal to 0.2wt.%;

[0046] The total amount of Sr and Zr is less than or equal to 0.15wt.%, and the Al content is adjusted so that the total amount of the 5 series aluminum alloy is 100wt.%.

[0047] Another technical solution provided by the present invention is: a 5 series aluminum alloy, which comprises, by weight percentage: 2.0wt.% to 3.2wt.% Mg, 0.05wt.% to 0.3wt.% Cu, 0.6wt.% to 1.2wt.% Mn, 0.05wt.% to 0.3wt.% Cr, 0.01wt.% to 0.3wt.% Zn, less than or equal to 0.15wt.% Ti, 0.02wt.% to 0.14wt.% Mo, 0.02wt.% to 0.14wt.% Zr, and impurities;

[0048] The impurities include Fe, Si and other impurities except Fe and Si; in terms of weight percentage, in the 5 series aluminum alloy, Fe is 0.4wt.% to 0.7wt.%, Si is 0.1wt.% to 0.4wt.%, and the total content of other impurities is less than or equal to 0.2wt.%;

[0049] The total amount of Mo and Zr is less than or equal to 0.15wt.%, and the content of Al is adjusted so that the total amount of the 5 series aluminum alloy is 100wt.%.

[0050] Another technical solution provided by the present invention is a 5 series aluminum alloy, which comprises, in terms of weight percentage, 2.0 wt.% to 3.2 wt.% of Mg, 0.05 wt.% to 0.3 wt.% of Cu, 0.4 wt.% to 1.2 wt.% of Mn, 0.05 wt.% to 0.3 wt.% of Cr, 0.01 wt.% to 0.3 wt.% of Zn, less than or equal to 0.15 wt.% of Ti, 0.01 wt.% to 0.08 wt.% of Sr, 0.01 wt.% to 0.08 wt.% of Mo, 0.01 wt.% to 0.08 wt.% of Zr, and impurities;

[0051] The impurities include Fe, Si and other impurities except Fe and Si; in terms of weight percentage, in the 5 series aluminum alloy, Fe is 0.35wt.% to 0.7wt.%, Si is 0.1wt.% to 0.4wt.%, and the total content of other impurities is less than or equal to 0.2wt.%;

[0052] The total amount of Sr, Mo and Zr is less than or equal to 0.15wt.%, and the content of Al is adjusted so that the total amount of the 5 series aluminum alloy is 100wt.%.

[0053] Another technical solution provided by the present invention is: a 5 series aluminum alloy, which comprises, by weight percentage: 2.0wt.% to 3.2wt.% Mg, 0.05wt.% to 0.3wt.% Cu, 0.4wt.% to 1.2wt.% Mn, 0.05wt.% to 0.3wt.% Cr, 0.01wt.% to 0.3wt.% Zn, less than or equal to 0.15wt.% Ti and impurities;

[0054] The impurities include Fe, Si and other impurities except Fe and Si; in terms of weight percentage, in the 5 series aluminum alloy, Fe is 0.35wt.% to 0.7wt.%, Si is 0.1wt.% to 0.4wt.%, and the total content of other impurities is less than or equal to 0.2wt.%;

[0055] The 5 series aluminum alloy further comprises two or three of Sr, Mo and Zr as additives, the content of the additives is less than or equal to 0.15wt.%, and the content of any one element in the additives is 0.1-10 times the content of the other elements;

[0056] The Al content is adjusted so that the total amount of the 5-series aluminum alloy is 100 wt.%.

[0057] Furthermore, in the additive, the content of any one element is 0.2-8 times the content of other elements.

[0058] Furthermore, in the additive, the content of any one element is 0.4-5 times the content of other elements, for example, 0.5 times, 0.6 times, 0.8 times, 1.0 times, 1.2 times, 1.5 times, 1.6 times, 2.0 times, 2.5 times, 3.0 times, 3.5 times, etc.

[0059] Another technical solution provided by the present invention is an aluminum alloy, which is prepared by the following method:

[0060] (1) providing a raw material containing at least 50wt.% of recycled aluminum alloy material, and sequentially performing smelting, first refining, alloying, second refining, and casting to produce an aluminum alloy ingot; wherein, in terms of weight percentage, the aluminum alloy contains: 2.0wt.% to 3.2wt.% Mg, 0.05wt.% to 0.3wt.% Cu, 0.4wt.% to 1.2wt.% Mn, 0.05wt.% to 0.3wt.% Cr, 0.01wt.% to 0.3wt.% Zn, less than or equal to 0.15wt.% Ti, 0 to 0.14wt.% Sr, 0 to 0.14wt.% Mo, 0 to 0.14wt.% Zr, and impurities;

[0061] The impurities include Fe, Si and other impurities except Fe and Si; in terms of weight percentage, in the aluminum alloy, Fe is 0.35wt.% to 0.7wt.%, Si is 0.1wt.% to 0.4wt.%, and the total content of other impurities is less than or equal to 0.2wt.%;

[0062] The Al content is adjusted so that the total amount of the aluminum alloy is 100wt.%;

[0063] At least two of the Sr, Mo and Zr are present at the same time, and the total amount of the Sr, Mo and Zr is less than or equal to 0.15wt.%;

[0064] (2) subjecting the aluminum alloy ingot to homogenization treatment at a temperature of 480-540° C. for 2-12 hours;

[0065] (3) After homogenization, hot rough rolling is carried out, the rolling passes are 12-18 times, the total deformation is greater than 93%, and the starting rolling temperature is greater than 400°C;

[0066] (4) After the hot rough rolling is completed, hot finishing rolling is performed, the total deformation is greater than 85%, and the final rolling temperature is greater than 330° C.;

[0067] (5) subjecting the hot-rolled material obtained after the treatment in step (4) to cold rolling with a deformation amount of 60% to 90%;

[0068] (6) Annealing is carried out in a box-type annealing furnace at a temperature of 320-400°C for 2-6 hours, or on a continuous annealing line, heating to 460-520°C for 0-120 seconds.

[0069] Another technical solution provided by the present invention is: use of the aluminum alloy described above in the preparation of automobile body parts, rail transit vehicle structures or ship structures.

[0070] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:

[0071] In order to meet the current demand for recycling and reuse of aluminum alloy waste in order to meet the needs of reducing carbon emissions and lowering production costs, the poor performance of aluminum alloys prepared from current aluminum alloy waste recycling, especially 5754 aluminum alloy, should be solved. For example, it is difficult to balance the tensile strength, yield strength and elongation after fracture. Based on a large number of experimental studies, the inventors innovatively provide an improved aluminum alloy formula. In the Al-Mg alloy system, Mn, Cr, Cu, Zn and selective X1-X3 elements (Sr, Mo, Zr) are used to compensate for the strength loss caused by the reduction of Mg element content. At the same time, in the system of the present invention, it is analyzed that the addition of Cr element can improve the morphology and size of the primary second phase particles in the aluminum alloy and refine the second phase particles; in addition, the addition of Cr element can also significantly improve the nucleation, precipitation and coarsening behavior of the dispersed phase during homogenization heat treatment, increase the number density of the dispersed phase, and reduce the size of the dispersed phase; further, in the system of the present invention, combined with the addition of X1-X3 elements, the purpose of significantly refining the size of the primary second phase particles and the grain size can be achieved, and X1-X3 elements can also precipitate small and uniformly distributed dispersed phase particles during homogenization heat treatment, such as Al 12 Mo, Al 38 Mg 58 Sr4, Al3Zr, etc. These dispersed phases can regulate the microstructure of the aluminum alloy sheet and play a role in dispersed phase strengthening, improve the forming performance and strength of the product, and at least achieve the balance of alloy properties such as tensile strength, yield strength and elongation after fracture. At the same time, in the preparation method of the present invention, by regulating the hot rolling deformation, especially controlling the deformation amount of a single pass in the first hot rolling process to make it greater than or equal to 5%, the second phase is destroyed and the second phase particle size is reduced, and further combined with the secondary hot rolling and cold rolling treatment, the alloy properties of the aluminum alloy of the present invention are further improved. Based on the above characteristics, even if recycled aluminum alloys (such as recycled cans, automobile plates, etc.) are used, aluminum alloys with medium strength and excellent formability can be produced, which can be used to replace 5754 aluminum alloys, not only saving energy and reducing emissions, but also reducing production costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0072] Figure 1 This is the metallographic photograph of the cast structure of AA5754 alloy;

[0073] Figure 2 This is the metallographic photograph of the cast structure of A1-1 alloy;

[0074] Figure 3 This is the metallographic photograph of the cast structure of A1-2 alloy;

[0075] Figure 4 This is the metallographic photograph of the cast structure of A1-3 alloy;

[0076] Figure 5 This is the metallographic photograph of the cast structure of A1-4 alloy;

[0077] Figure 6 This is the metallographic photograph of the cast structure of A2 alloy;

[0078] Figure 7 This is the metallographic photograph of the cast structure of A3 alloy;

[0079] Figure 8 This is the metallographic photograph of the cast structure of A4 alloy;

[0080] Fig. 9 This is the metallographic photograph of the cast structure of A5 alloy;

[0081] Fig.10 This is the metallographic photograph of the cast structure of A6 alloy;

[0082] Fig.11 This is the metallographic photograph of the cast structure of A7 alloy;

[0083] Fig.12 This is the metallographic photograph of the cast structure of A8 alloy;

[0084] Fig.13 It is a bar graph of the area percentage of the iron-rich phase in the as-cast state of AA5754, A1-1 to A1-4, A2 to A8 alloys;

[0085] Fig.14 is a bar graph of the average equivalent diameter of the iron-rich phase in the as-cast state of AA5754, A1-1 to A1-4, A2 to A8 alloys;

[0086] Fig.15 The bar graph is a graph showing the area percentage of the Mg2Si phase in the as-cast state of AA5754, A1-1 to A1-4, A2 to A8 alloys;

[0087] Fig.16 The bar graph is a graph of the average equivalent diameter of the Mg2Si phase in the as-cast state of AA5754, A1-1 to A1-4, A2 to A8 alloys;

[0088] Fig.17 This is the metallographic photo of AA5754-H1 alloy after homogenization treatment;

[0089] Fig.18 This is the metallographic photo of AA5754-H2 alloy after homogenization treatment;

[0090] Fig.19 This is the metallographic photograph of the A1-1-H1 alloy after homogenization treatment;

[0091] Fig. 20 This is the metallographic photograph of the A1-1-H2 alloy after homogenization treatment;

[0092] Fig.21 This is the metallographic photograph of the A1-2-H alloy after homogenization treatment;

[0093] Fig. 22 This is the metallographic photograph of the A1-3-H alloy after homogenization treatment;

[0094] Fig.23 This is the metallographic photograph of the A1-4-H alloy after homogenization treatment;

[0095] Fig.24 This is the metallographic photograph of A2-H alloy after homogenization treatment;

[0096] Fig.25 This is the metallographic photograph of A3-H alloy after homogenization treatment;

[0097] Fig.26 This is the metallographic photograph of A4-H alloy after homogenization treatment;

[0098] Fig. 27 This is the metallographic photograph of A5-H alloy after homogenization treatment;

[0099] Fig.28 This is the metallographic photograph of A6-H alloy after homogenization treatment;

[0100] Fig.29 This is the metallographic photograph of A7-H alloy after homogenization treatment;

[0101] Fig.30 This is the metallographic photograph of A8-H alloy after homogenization treatment;

[0102] Fig.31 This is the dispersed phase metallographic photo of AA5754-H1 alloy after homogenization treatment;

[0103] Fig.32 This is the metallographic photograph of the dispersed phase of the A1-1-H1 alloy after homogenization treatment;

[0104] Fig.33 This is the metallographic photograph of the dispersed phase of A2-H alloy after homogenization treatment;

[0105] Fig.34 The bar graph is a graph of the average equivalent diameter of the iron-rich phase after the alloys of AA5754-H1, AA5754-H2, A1-1-H1, A1-1-H2, A1-2-H to A1-4-H, A2-H to A8-H are processed into the final product. DETAILED DESCRIPTION

[0106] The present invention provides an aluminum alloy product and a processing technology thereof with significant performance improvement, especially in terms of tensile strength, yield strength and elongation after fracture. The aluminum alloy of the present invention overcomes the deterioration of alloy performance caused by high content of impurity iron, especially reduces and / or eliminates the amplification effect of the negative impact of impurity Fe on Mn and Si when the impurity Fe, impurity Si and Mn are simultaneously at high content, thereby fundamentally avoiding the deterioration of alloy performance.

[0107] The performance of aluminum alloys mainly depends on the alloy composition, which directly determines the most basic properties of the alloy, such as mechanical properties, forming properties, etc. Further, in some embodiments, the recycled aluminum alloy will inevitably contain Si elements and form a coarse Mg2Si phase during the casting process, which seriously deteriorates the forming properties; at the same time, in addition to introducing high content of Fe and Si elements, the recycled material will also introduce a large amount of Mn elements, which will promote the coarse Al x The formation of (Fe, Mn, Cr) or Al(Fe, Mn, Cr)Si phase significantly deteriorates the forming properties. Generally, although Cu can make up for the insufficient strength caused by the reduction of Mg content, Cu combines with Fe to form refractory Al7Cu2Fe phase. The coarse Al7Cu2Fe phase will further deteriorate the forming properties of the alloy. In addition, Cu will also form coarse S phase (i.e. Al2CuMg phase) with Mg or directly form coarse Al2Cu phase, which will reduce the forming properties of the alloy.

[0108] The present invention at least solves the above-mentioned problems by adjusting the combination of formula ingredients and controlling the content, and further improves the alloy properties by optimizing the preparation method. Based on the concept of the present invention, it is possible to produce aluminum alloys using recycled aluminum alloy waste, and exhibit good mechanical properties and forming properties. The aluminum alloy itself is highly recyclable and has a significant advantage in reducing carbon emissions from aluminum alloy production.

[0109] Aluminum alloy composition:

[0110] In some embodiments, the aluminum alloy described in the present invention may have the element composition shown in Table 1.

[0111]

[0112] Preparation method:

[0113] Using waste aluminum such as can materials as raw materials, melting it in a smelting furnace to 740-790° C. to obtain an aluminum alloy melt; further preferably, selectively adding intermediate alloys such as Al-Mn, Al-Cr, Al-Mo, Al-Zr, Al-Sr, and Mg ingots to obtain an aluminum alloy melt with qualified composition;

[0114] Specifically, the raw materials are sequentially subjected to smelting, first refining, alloying, second refining, and casting to obtain an aluminum alloy ingot having a target aluminum alloy composition;

[0115] The smelting process parameters are as follows: firstly, the recycled aluminum alloy such as can material is added into a smelting furnace with a small amount of electrolytic aluminum water or original aluminum ingot as raw materials and melted to 740-790℃ to obtain aluminum alloy melt;

[0116] The process parameters of the first refining are as follows: the first refining is carried out in the range of 735-745°C, electromagnetic stirring is turned on during the refining process, a granular refining agent is used for refining (the amount is 1wt.%-2.5wt.% of the aluminum alloy melt), and the refining agent can be a refining agent commonly used in melt refining in the aluminum processing industry (for example, NaCl, KCl, MgCl2, BaCl2, MgO, KAlF4, Na3AlF6, CaF2, etc.), and after the refining is completed, it is allowed to stand for more than 30 minutes, and then the slag on the surface of the melt is slowly scraped out using a slag scraping tool, and the melt is prevented from being disturbed during the slag scraping process to obtain a pure aluminum alloy melt;

[0117] The alloying process parameters are as follows: sampling the aluminum alloy melt for component pre-analysis, selectively adding master alloys such as Al-Mn, Al-Cr, Al-Mo, Al-Zr, Al-Sr and Mg ingots according to the component detection results, and starting electromagnetic stirring for more than 15 minutes to obtain an aluminum alloy melt with uniform and qualified composition;

[0118] The process parameters for the second refining are as follows: after alloying, the aluminum alloy melt is poured into a holding furnace for the second refining, the melt temperature is controlled at 730-750°C, the refining medium is high-purity argon (purity greater than or equal to 99%) and high-purity chlorine (purity greater than or equal to 99%), and the argon flow rate is 10-25Nm 3 / h, chlorine flow rate 4~8Nm 3 / h, rotor speed 220-280rpm, refining for more than 30min, after refining, slag is removed to ensure that there is no large slag on the melt surface;

[0119] The casting process parameters are as follows: the casting temperature is controlled at 705-725℃, the casting speed is 40-60mm / min, the Ti element is introduced in the form of Al-5Ti-1B for grain refinement, the addition position is added in the flow channel between the holding furnace and the casting machine using an online addition method, and the wire feeder speed is calculated according to the amount of Ti element added in the melt to obtain a qualified aluminum alloy ingot;

[0120] The above ingot is subjected to homogenization treatment: the aluminum alloy ingot is subjected to homogenization treatment at 480-540° C. for 2-12 hours;

[0121] After homogenization, hot rough rolling is carried out, the rolling passes are 12-18 times, the total deformation is greater than 93%, and the starting rolling temperature is greater than 400°C;

[0122] After the hot rough rolling is completed, hot finishing rolling is carried out, the total deformation is greater than 85%, and the final rolling temperature is greater than 330℃;

[0123] The hot rolled material obtained after the hot rough rolling is subjected to cold rolling deformation with a deformation amount of 60%-90%;

[0124] Annealing is carried out in a box-type annealing furnace at a temperature of 320-400°C for 2-6 hours, or on a continuous annealing line, heating to 460-520°C for 0-120 seconds.

[0125] The above scheme is further described below in conjunction with specific embodiments; it should be understood that these embodiments are used to illustrate the basic principles, main features and advantages of the present invention, and the present invention is not limited to the scope of the following embodiments; the implementation conditions adopted in the embodiments can be further adjusted according to specific requirements, and the implementation conditions not specified are usually the conditions in conventional experiments.

[0126] Unless otherwise specified in the following examples, all raw materials are commercially available or prepared by conventional methods in the art.

[0127] Examples 1-7 and Comparative Examples 1-5:

[0128] In order to determine the properties of the aluminum alloy of the present invention, the AA5754 alloy, A1-1, A1-2, A1-3, A1-4, A2~A8 alloys in Table 2 were prepared according to the method of the present invention. As shown in Table 2, the AA5754 alloy is a typical 5754 alloy composition in the AA (American Aluminum Association) standard, A1-1, A1-2, A1-3, A1-4 are 5 series aluminum alloys with high Fe, Si, and Mn elements prepared using recycled materials, and A2~A8 are new 5 series aluminum alloys described in the present invention.

[0129]

[0130] The preparation method comprises:

[0131] Firstly, the can waste aluminum is added into a smelting furnace with a small amount of electrolytic aluminum water or original aluminum ingot as raw materials and melted to 760±5℃ to obtain aluminum alloy melt;

[0132] The first refining was carried out at 740±5℃, and electromagnetic stirring was turned on during the refining process. A granular refining agent (NaCl, the amount of which was 1.5wt.% of the aluminum alloy melt) was used for refining. After the refining was completed, the slag was left to stand for more than 30 minutes, and then the slag on the surface of the melt was slowly scraped off with a slag scraping tool. The melt was not disturbed during the slag scraping process to obtain a pure aluminum alloy melt.

[0133] The alloying process parameters are as follows: sampling the above aluminum alloy melt for component pre-analysis, selectively adding Al-Mn, Al-Cr, Al-Mo, Al-Zr, Al-Sr, Al-Sc and other intermediate alloys and Mg ingots according to the component detection results, and starting electromagnetic stirring for more than 15 minutes to obtain an aluminum alloy melt with uniform and qualified composition;

[0134] The process parameters for the second refining are as follows: after alloying, the aluminum alloy melt is poured into a holding furnace for the second refining, the melt temperature is controlled at 740±5℃, the refining medium is high-purity argon and high-purity chlorine, and the argon flow rate is 15Nm 3 / h, chlorine gas flow rate 5Nm 3 / h, rotor speed 250rpm, refining for more than 30min, after refining, slag is removed to ensure that there is no large slag on the melt surface;

[0135] The casting process parameters are as follows: the casting temperature is controlled at 715±5℃, the casting speed is 48mm / min, the Ti element is introduced in the form of Al-5Ti-1B for grain refinement, the addition position is added in the flow channel between the holding furnace and the casting machine using an online addition method, and the wire feeder speed is calculated according to the amount of Ti element added in the melt to obtain an aluminum alloy ingot with a target aluminum alloy composition;

[0136] The above-mentioned ingot is homogenized. The aluminum alloy ingot is homogenized at 480-540° C. for 2-12 hours. The homogenization process of each embodiment and comparative example is shown in Table 3.

[0137]

[0138] The aluminum alloy ingot is firstly subjected to hot rough rolling, the hot rolling start temperature is 450°C, and hot rolled to an intermediate billet through 14 passes, and the hot rough rolling deformation is 95%;

[0139] The intermediate billet is subjected to hot finishing rolling, the hot finishing rolling deformation is 90%, and the final rolling temperature is 340°C;

[0140] The hot rolled coil is cold rolled to 1 mm, with a cold rolling deformation of 75%;

[0141] The cold rolled coil is annealed in a box-type annealing furnace at 360° C. for 3 hours to obtain a sheet-shaped aluminum alloy.

[0142] Performance Testing:

[0143] (1) See Figures 1 to 12 , the metallographic photos of the cast structure of each alloy in Table 2 are given. Figure 13~Figure 16 The statistical results of the area percentage and average equivalent diameter of the Fe-rich phase and Mg2Si phase in the alloy cast structure are given respectively. Since the Si, Fe, and Mn contents in the conventional AA5754 alloy are relatively low, its cast structure contains only a small amount of Mg2Si and Fe-rich phases. Compared with the AA5754 alloy (Comparative Example 1), the Fe-rich phase content and equivalent diameter of the A1-1 alloy (Comparative Example 2) with high Fe and Mn content increased to about 4.4% and 6μm, respectively. It can be seen that coarse second phase particles will seriously damage the forming properties of the alloy.

[0144] The total content of Sr+Mo in Comparative Example 3 is 0.3wt%, and the contents of other elements are the same as those in Example 1. Figure 3 It can be seen that although the iron-rich phase is refined to a certain extent, with the increase of Sr+Mo content, large blocks of Al 12 Mo phase and Al4Sr phase, which have a high formation temperature, are difficult to dissolve back during the subsequent heat treatment process, and are also difficult to break by rolling. The coarse second phase will inevitably lead to a decrease in the mechanical properties and plasticity of the alloy.

[0145] In Comparative Example 4, no Sr or Mo element was added, only 0.1% Zr element was added, and the remaining components were the same as those in Example 1. Figure 4 It can be seen that the addition of Zr alone has almost no refining effect on the Fe-rich phase and Mg2Si phase.

[0146] Comparative Example 5 shows the changes in the alloy structure when Zr+Sc is microalloyed. Figure 5 As shown, there are Fe-rich phase and Mg2Si phase with coarse size and complex morphology in the alloy.

[0147] The A2-A8 alloys produced by the present invention still contain a large amount of Fe, Si and Mn elements in the alloys prepared from recycled materials. However, the A2-A8 alloys have a significant change in their cast structure compared with the A1-1 alloy due to the optimization of alloy composition. Figure 6~Figure 12 ; The content and average equivalent diameter of Fe-rich phase and Mg2Si phase in the alloy decreased significantly, see Figure 13~Figure 16 Statistics.

[0148] (2) See Figure 17-Figure 30, it can be clearly seen that the evolution of the Fe-rich phase and Mg2Si phase after homogenization treatment of all alloys in Comparative Examples 1 to 5 and Examples 1 to 7. Even though the AA5754 alloy has extremely low Si and Fe contents, the Fe-rich phase and Mg2Si phase cannot be completely dissolved back after homogenization treatment (two homogenization treatment processes, AA5754-H1 alloy and AA5754-H2 alloy are obtained respectively), and the Mg2Si phase content even has an increasing trend. Due to the increase of Fe, Mn, and Si elements, the content and size of the Fe-rich phase and Mg2Si phase in the A1-1 to A1-4 alloys are significantly increased compared with the AA5754 alloy, and there is no obvious change after homogenization treatment (after homogenization treatment, A1-1-H1 alloy, A1-1-H2 alloy, A1-2-H alloy, A1-3-H alloy, and A1-4-H alloy are obtained respectively). However, the A2-A8 alloys produced by the present invention (after homogenization treatment, A2-H alloys to A8-H alloys were obtained) showed a significantly different change pattern, and the content of the iron-rich phase after homogenization treatment was significantly reduced compared with the cast alloy. In addition, the presence of the Mg2Si phase, which was almost difficult to observe, can be observed in the A2-A8 alloys after homogenization treatment.

[0149] See also Figure 31~Figure 33 It can be seen that after the alloy of the present invention is homogenized, the uniformity of the dispersed phase distribution is significantly increased, the number density is increased, and the dispersed phase size is reduced. For details, see Fig.33 A2-H alloy; while the dispersed phase density in AA5754-H1 is significantly reduced and severely coarsened (see Fig.31 ), although A1-1-H1 has a high number density of dispersed phase, its distribution is obviously different. There is an obvious low number density and coarse area of ​​dispersed phase in the center of the grain (see Fig.32 ).

[0150] (3) See Fig.34 As shown, the average equivalent diameter of the second phase particles of the A2-A8 alloys produced by the method of the present invention after rolling is about 0.8-1.5 μm, which is much lower than the average equivalent diameter of the second phase particles of several alloys in the comparative example. The cold-rolled final thickness product is annealed, and the plate is processed into an O state to obtain the final product. The final product is tested for tensile properties according to ISO 6892 standard, and the results are shown in Table 4.

[0151]

[0152] It can be seen from Table 4 that the A2-A8 alloys produced by the present invention exhibit higher mechanical properties than the conventional 5754 alloy, and have similar elongation after fracture. However, the yield strength and tensile strength of the A1-1 alloy to the A1-4 alloy, and the A1-1 alloy to the A1-3 alloy with high Fe, Mn, and Si content are significantly lower than the A2-A8 alloys produced by the present invention, especially the plasticity of the A1-1 alloy to the A1-4 alloy is significantly reduced, which is difficult to meet the requirements.

[0153] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

[0154] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

Claims

1. An aluminum alloy, characterized in that: In terms of weight percentage, the aluminum alloy comprises: 2.0wt.% to 3.2wt.% Mg, 0.05wt.% to 0.3wt.% Cu, 0.4wt.% to 1.2wt.% Mn, 0.05wt.% to 0.3wt.% Cr, 0.01wt.% to 0.3wt.% Zn, less than or equal to 0.15wt.% Ti, 0 to 0.14wt.% X1, 0 to 0.14wt.% X2, 0 to 0.14wt.% X3, and impurities; The impurities include Fe, Si and other impurities except Fe and Si; in terms of weight percentage, in the aluminum alloy, Fe is 0.45wt.% to 0.7wt.%, Si is 0.1wt.% to 0.4wt.%, and the total content of other impurities is less than or equal to 0.2wt.%; The Al content is adjusted so that the total amount of the aluminum alloy is 100wt.%; Wherein, the X1, X2, and X3 are independently selected from Sr, Mo, and Zr, the X1, X2, and X3 are different and at least two of them exist at the same time, and the total amount of the X1, X2, and X3 is less than or equal to 0.15wt.%; In the alloy structure of the aluminum alloy in the O state, the average equivalent diameter of the iron-rich phase is 0.8-1.5 μm; In the process of preparing the aluminum alloy, at least 50 wt. % of recycled aluminum alloy materials are used to prepare the aluminum alloy melt.

2. The aluminum alloy according to claim 1, characterized in that In the cast structure of the aluminum alloy, the area percentage of the iron-rich phase is less than or equal to 3.5%, and the average equivalent diameter is less than or equal to 3.5 μm.

3. The aluminum alloy according to claim 1, characterized in that In the cast structure of the aluminum alloy, the area percentage of the Mg2Si phase is less than or equal to 1.5%, and the average equivalent diameter is less than or equal to 1.2 μm.

4. The aluminum alloy according to claim 1, characterized in that The alloy structure of the aluminum alloy includes dispersed particles, and the dispersed particles include: (1) A combination of one or more selected from Al6Mn dispersed phase particles, Al4Mn dispersed phase particles, Al6(FeMn) dispersed phase particles, Al(FeMnCr)Si dispersed phase particles, and Al7Cr dispersed phase particles; (2) Selected from Al 12 Mo dispersed phase particles, Al 38 Mg 58 Two or three of Sr4 dispersed phase particles and Al3Zr dispersed phase particles.

5. The aluminum alloy according to claim 4, characterized in that The average equivalent diameter of the dispersed particles is less than or equal to 100 nm, and the number density of the dispersed particles is 5-20 / μm 2 .

6. The aluminum alloy according to claim 1, characterized in that The total amount of Mg, Cu and Mn is greater than or equal to 2.5 wt.%.

7. The aluminum alloy according to claim 1 or 6, characterized in that: The ratio of the total amount of Mg and Mn to the content of Cr is 10-70:

1.

8. The aluminum alloy according to claim 1 or 6, characterized in that: The ratio of Mg content to Cu content is 8-55:

1.

9. The aluminum alloy according to claim 1 or 6, characterized in that: The aluminum alloy has a yield strength of greater than or equal to 140 MPa, a tensile strength of greater than or equal to 260 MPa, and an elongation after fracture of greater than or equal to 20% in the O state.

10. The aluminum alloy according to claim 9, characterized in that The aluminum alloy has a yield strength of greater than or equal to 145 MPa, a tensile strength of greater than or equal to 260 MPa, and an elongation after fracture of greater than or equal to 21.5% in the O state.

11. The aluminum alloy according to any one of claims 1 to 6, characterized in that: The aluminum alloy is a 5 series aluminum alloy.

12. The aluminum alloy according to claim 1, characterized in that In terms of weight percentage, the aluminum alloy comprises: 2.0wt.% to 3.0wt.% Mg, 0.05wt.% to 0.3wt.% Cu, 0.5wt.% to 1.2wt.% Mn, 0.05wt.% to 0.3wt.% Cr, 0.05wt.% to 0.25wt.% Zn, less than or equal to 0.1wt.% Ti, 0 to 0.12wt.% X1, 0 to 0.12wt.% X2, 0 to 0.12wt.% X3, 0.45wt.% to 0.7wt.% Fe, 0.15wt.% to 0.4wt.% Si, and less than or equal to 0.15wt.% other impurities, and the Al content is adjusted so that the total amount of the aluminum alloy is 100wt.%.

13. The aluminum alloy according to claim 12, characterized in that In terms of weight percentage, the aluminum alloy comprises: 2.0wt.% to 3.0wt.% Mg, 0.05wt.% to 0.3wt.% Cu, 0.6wt.% to 1.0wt.% Mn, 0.05wt.% to 0.3wt.% Cr, 0.15wt.% to 0.25wt.% Zn, 0.02wt.% to 0.06wt.% Ti, 0.01wt.% to 0.12wt.% X1, 0.01wt.% to 0.12wt.% X2, 0.01wt.% to 0.12wt.% X3, 0.45wt.% to 0.7wt.% Fe, 0.15wt.% to 0.4wt.% Si, and less than or equal to 0.15wt.% of other impurities, and the Al content is adjusted so that the total amount of the aluminum alloy is 100wt.%.

14. A method for preparing the aluminum alloy according to any one of claims 1 to 13, characterized in that: The preparation method comprises: Providing an aluminum alloy melt containing at least 50 wt.% of recycled aluminum alloy material, and forming the aluminum alloy melt into an aluminum alloy ingot; Performing homogenization treatment on the aluminum alloy ingot to obtain a first intermediate; Performing a first hot rolling on the first intermediate, and controlling the deformation amount of a single pass of the first hot rolling to be greater than or equal to 5%, and the total deformation amount to be greater than or equal to 90%, to obtain a second intermediate; Performing a second hot rolling on the second intermediate, controlling the total deformation to be greater than or equal to 85%, to obtain a third intermediate; The third intermediate is subjected to cold rolling deformation with a deformation amount of 60% to 90%; Annealing treatment.

15. The method for preparing an aluminum alloy according to claim 14, characterized in that: The content of recycled aluminum alloy material in the aluminum alloy melt is greater than or equal to 70%.

16. The method for preparing an aluminum alloy according to claim 15, characterized in that: The content of recycled aluminum alloy material in the aluminum alloy melt is greater than or equal to 95%.

17. The method for preparing an aluminum alloy according to claim 14, characterized in that: In the first hot rolling, the deformation amount of a single pass is greater than or equal to 6%, and the total deformation amount is greater than or equal to 93%; and / or, in the second hot rolling, the total deformation amount is controlled to be greater than or equal to 88%.

18. The method for preparing an aluminum alloy according to claim 14, characterized in that: The homogenization treatment temperature is 480-540°C and the treatment time is 2-12h; In the first hot rolling, the starting rolling temperature is 400-500° C.; in the second hot rolling, the finishing rolling temperature is 320-360° C.; The annealing temperature of the annealing treatment is 320-400° C. and the temperature is kept for 2-6 hours. Alternatively, the annealing treatment is carried out on a continuous annealing line, heated to 460-520° C. and kept for 0-120 seconds.

19. An aluminum alloy, characterized in that: The aluminum alloy is prepared by the following method: (1) providing a raw material containing at least 50wt.% of recycled aluminum alloy material, and sequentially performing smelting, first refining, alloying, second refining, and casting to produce an aluminum alloy ingot; wherein, in terms of weight percentage, the aluminum alloy contains: 2.0wt.% to 3.2wt.% Mg, 0.05wt.% to 0.3wt.% Cu, 0.4wt.% to 1.2wt.% Mn, 0.05wt.% to 0.3wt.% Cr, 0.01wt.% to 0.3wt.% Zn, less than or equal to 0.15wt.% Ti, 0 to 0.14wt.% Sr, 0 to 0.14wt.% Mo, 0 to 0.14wt.% Zr, and impurities; The impurities include Fe, Si and other impurities except Fe and Si; in terms of weight percentage, in the aluminum alloy, Fe is 0.45wt.% to 0.7wt.%, Si is 0.1wt.% to 0.4wt.%, and the total content of other impurities is less than or equal to 0.2wt.%; The Al content is adjusted so that the total amount of the aluminum alloy is 100wt.%; At least two of the Sr, Mo and Zr are present at the same time, and the total amount of the Sr, Mo and Zr is less than or equal to 0.15wt.%; (2) subjecting the aluminum alloy ingot to homogenization treatment at a temperature of 480-540° C. for 2-12 hours; (3) hot rough rolling, with 12-18 passes, a total deformation greater than 93%, and a starting rolling temperature greater than 400°C; (4) hot finishing rolling, with a total deformation greater than 85% and a final rolling temperature greater than 330°C; (5) cold rolling with a deformation amount of 60%-90%; (6) Annealing is carried out in a box-type annealing furnace at a temperature of 320-400°C for 2-6 hours, or on a continuous annealing line, heating to 460-520°C for 0-120 seconds.

20. Use of the aluminum alloy according to any one of claims 1 to 13, or the aluminum alloy according to claim 19, in the preparation of automobile body parts, rail transportation vehicle structures or ship structures.

Citation Information

Patent Citations

  • Method for improving O-state conductivity of 5754 alloy

    CN113337760A

  • Image processing method, device and equipment and computer readable storage medium

    CN117011913A

  • High-performance low-carbon secondary aluminum extruded profile and preparation method thereof

    CN115261649A